Experience note: micropractice as an investigative path in the teaching of color based on the studies of Josef Albers (Revista Apotheke, 2023)
In this text we seek to present the results of a micropractice carried out based on the studies of the interaction of color by Josef Albers at the State University of Londrina, for this we opted for the format of an experience note. To do so, at first, we highlight the meaning of the term micropractice developed by Apotheke Painting Studio, as well as a presentation of some elements of the teaching approach to the visual arts developed by the German artist teacher Josef Albers. Secondly, we describe the action taken and the results achieved.
Keywords: Josef Albers; visual arts teaching; teacher artist; micropractice